2008
DOI: 10.1021/es071989t
|View full text |Cite
|
Sign up to set email alerts
|

Reductive Debromination of Polybrominated Diphenyl Ethers in Anaerobic Sediment and a Biomimetic System

Abstract: Because of the bioaccumulation of penta- and tetrapolybrominated diphenyl ether (PBDE) flame retardants in biota,the environmental biotransformation of decabromodiphenyl ether (BDE-209) is of interest. BDE-209 accounts for more than 80% by mass of PBDE production and is the dominant PBDE in sediments. Most sediments are anaerobic and reports of microbial reductive dehalogenation of hydrophobic persistent organohalogen pollutants are numerous. Reductive debromination of BDE-209 in the environment could provide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
106
2
3

Year Published

2011
2011
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 218 publications
(120 citation statements)
references
References 26 publications
8
106
2
3
Order By: Relevance
“…Degradation of different PBDE congeners occurred at rates corresponding to bromine substitution levels and the kinetic constant k (h À1 ) was in the following order: BDE-28 (0.00095-0.0078) < BDE-47 (0.0016-0.0079) < BDE-99 (0.0011-0.017) < BDE-209 (0.0016-0.019) ( Table S2 in the Supplementary material). BDE-209 degraded faster than BDE-99 and BDE-99 faster than BDE-47, very similar to the results obtained for PBDE debromination in a biomimetic experimental system using coenzyme vitamin B12, in which PBDEs underwent reductive debromination reactions at rates corresponding to the number of bromine substitutions (Tokarz et al, 2008). Among plant species, enzyme solution from maize roots degraded PBDEs more obviously than the ones from pumpkin and ryegrass roots, which is speculated to be ascribed to the difference in metabolic enzyme activity of different plant species (Chhikara et al, 2010).…”
Section: In Vitro Biodegradation Of Pbdes By Root Crude Enzymessupporting
confidence: 84%
“…Degradation of different PBDE congeners occurred at rates corresponding to bromine substitution levels and the kinetic constant k (h À1 ) was in the following order: BDE-28 (0.00095-0.0078) < BDE-47 (0.0016-0.0079) < BDE-99 (0.0011-0.017) < BDE-209 (0.0016-0.019) ( Table S2 in the Supplementary material). BDE-209 degraded faster than BDE-99 and BDE-99 faster than BDE-47, very similar to the results obtained for PBDE debromination in a biomimetic experimental system using coenzyme vitamin B12, in which PBDEs underwent reductive debromination reactions at rates corresponding to the number of bromine substitutions (Tokarz et al, 2008). Among plant species, enzyme solution from maize roots degraded PBDEs more obviously than the ones from pumpkin and ryegrass roots, which is speculated to be ascribed to the difference in metabolic enzyme activity of different plant species (Chhikara et al, 2010).…”
Section: In Vitro Biodegradation Of Pbdes By Root Crude Enzymessupporting
confidence: 84%
“…4(a)) which were equivalent to the total of nonabromodiphenyl ethers concentrations in technical PBDE-209 reported in the literature (Tokarz et al, 2008). In this work, two nonabromodiphenyl ethers were formed in the incubation process with the decrease of PBDE-209, demonstrating that the degradation of PBDE-209 by P. aeruginosa was accompanied by debromination.…”
Section: Presence and Formation Of Lower Brominated Congenerssupporting
confidence: 66%
“…Microbial reductive debromination of BDE-209 and octa-BDEs mixtures under pure culture conditions has also been reported [36,37]. Furthermore, a recent study showed that BDE-209 may be degraded by microorganisms in anaerobic sediment to lessbrominated congeners, such as BDE-99, -47, and -66, and that BDE-99/-47 can also be transformed to BDE-28, BDE-17 by reductive debromination [38]. In the present study, the PCA results also indicated that some tri-and tetra-BDEs (BDE-17, -28, -66 and -71) accounted for 13.4% of the total variance (Fig.…”
Section: Principal Component Analysis Of Pbde Congener Profilesmentioning
confidence: 86%